HPLC-DAD ESTIMATION OF UNDECLARED SYNTHETIC COMPOUNDS IN SELECTED INDIAN HERBAL FORMULATIONS - Garg, Munish; Hooda, Monika (Asian Journal of Pharmaceutical Research and Development, 2013)
The present investigation was carried out to detect the most common synthetic compounds in selected Indian herbal formulations using high-pressure liquid chromatography-diode array detector (HPLC-DAD) and to compile an ultraviolet (UV) library to detect more than 50 synthetic compounds by comparing the analytical data (UV spectra, retention time, relative retention time) with those of the standards for future use. Twenty nine Indian herbal formulations comprising analgesics, anti-diabetics and slimming products were subjected for HPLC-DAD analysis followed by UV spectra comparison with the standard compound. Results revealed that marketed formulations with no specification of undeclared drugs on their label were analysed out of which three formulations were found to contain synthetic compounds. Overlapped UV spectra were found to be > 97 %. It is concluded that development and implementation of more such analytical methods for the quality control of herbal formulations is strongly recommended. Additionally, implementation of stricter regulatory requirements regarding labelling of herbal formulations is suggested.